Real-time cutting simulation in virtual reality systems based on the measurement of porcine organs. (December 2017) - Bao, YiDong; Wu, DongMei
A virtual soft tissues cutting model consistent with the organ specificity of real soft tissues was established in this paper, which was applied to the virtual operation training system. A measurement platform of soft tissue organ was designed and built, and the stress–strain and stress–relaxation data of pig liver and kidney were experimentally measured. Then, using the viscoelasticity mathematical formula, an improved virtual cutting model of the meshless classified balls-filling was constructed through VC++ and OpenGL. The cutting performance of the virtual soft tissues was further increased by leveraging the improved cutting classification algorithm. Finally, the extrusion and cutting simulation was enabled through the force feedback device, and the accuracy and effectiveness of this cutting model were validated by a comparative study of the virtual soft tissues cutting model and the stress–strain and stress–relaxation data of pig liver and kidney.